Rotor autocentering and speed control of hybrid bearingless SRM using single-neuron adaptive PID controller - V.S.Sobhan, Polamraju; V. Nagesh Kumar, G; V. Ramana Rao, P (International Journal of Engineering and Technology, 2018)
The bearingless switched reluctance motor (BLSRM) is emerging as an attractive option for modern industrial applications because of the features, such as compact size, lubrication and seal free performance, long lifeand ability to rotate at very high speed and high power. The control approach is extremely fundamental to a steady operation because of itshighly nonlinear, multi variable and open loop unstable nature. This paper presents a single neuron based rotor suspension control of a 12/14 Hybrid Pole BLSRM with autonomous rotation and suspension poles. This hybrid pole structure produces the suspension force linearly with respect to rotor position and independent of the torque characteristics. Implementation of a non model based Single neuron adaptive PID Controller by avoiding the modeling complexity is proposed. Experimental results demonstrate that the proposed controller maintains the rotor in the center position as well as the speed tracking and disturbance elimination performances independently.